Detecting Spam Review through Spammer’s Behavior Analysis - Naveed HUSSAIN; Hamid Turab MIRZA; Ibrar HUSSAIN (Advances in Distributed Computing and Artificial Intelligence Journal, 2020)
Online reviews about the purchase of a product or services provided have become the main source of user opinions. To gain profit or fame usually spam reviews are written to promote or demote some target products or services. This practice is known as review spamming. In the last few years, different methods have been suggested to solve the problem of review spamming but there is still a need to introduce new spam review detection method to improve accuracy results. In this work, researchers have studied six different spammer behavioral features and analyzed the proposed spam review detection method using weight method. An experimental evaluation was conducted on a benchmark dataset and achieved 84.5% accuracy.